1993
DOI: 10.1002/abio.370130302
|View full text |Cite
|
Sign up to set email alerts
|

The auxiliary substrate concept — an approach for overcoming limits of microbial performances

Abstract: and OutlookIn biotechnological processes, fundamental performances of microorganisms are used. The economy of these processes is essentially determined by the efficiency, velocity (productivity) and quality of thc products. Therefore it is a permanent task and challenge for basic and biotechnological research to seek out measures for improving the actually attained parameters. The auxiliary substrate concept supplics an approach. It is based on the fact that chemo-organo-heterotrophic substrates differ in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…The calculations were performed on the basis of the Y ATP concept (1,22), taking into account a biomass synthesis efficiency of 10.5 g of bacterial dry mass/mol of ATP (3). Biomass synthesis was assumed to start from a central carbon precursor (29), which is considered to be 3-phosphoglycerate (PGA).…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed on the basis of the Y ATP concept (1,22), taking into account a biomass synthesis efficiency of 10.5 g of bacterial dry mass/mol of ATP (3). Biomass synthesis was assumed to start from a central carbon precursor (29), which is considered to be 3-phosphoglycerate (PGA).…”
Section: Methodsmentioning
confidence: 99%
“…Since part of the glucose has to be used for the generation of ATP equivalents in dissimilation, it can be called an energy-deficient substrate (4). Due to this intrinsic free energy deficiency, experimentally obtained biomass yields on glucose are generally lower than the maximum biomass yield that could theoretically be reached when assimilatory reactions are fully optimized (5,9).…”
mentioning
confidence: 97%
“…An increase of the carbon source-to-biomass conversion efficiency has been demonstrated for many combinations of carbon sources and auxiliary substrates, including acetate-thiosulfate (14), acetate-formate (11), and glucose-formate (9,13,16). Formate is a suitable model auxiliary energy substrate for yeasts and fungi, as many of these organisms contain an NAD ϩ -linked formate dehydrogenase (EC 1.2.1.1; FDH) that catalyzes the oxidation of formate to CO 2 but are unable to assimilate formate (3,4,10,16,28,33,38). The NADH formed in the FDH reaction can be coupled to the mitochondrial respiratory chain and thus lead to ATP production.…”
mentioning
confidence: 99%
“…It has been suggested that this deˆciency could be overcome by providing an additional energy source, such as formate. 16) However, the addition of formate did not increase the yield signiˆcantly. Growth remained low: between 2 mg W l ・d (100 mM MeOH as sole substrate) and 7 mg W l ・d (100 mM MeOH+10 mM Ft).…”
Section: Resultsmentioning
confidence: 99%